Zonal variation in primary cilia elongation correlates with localized biomechanical degradation in stress deprived tendon. Issue 12 (23rd March 2016) - Rowson, Daniel; Knight, Martin M.; Screen, Hazel R.C.
ABSTRACT: Tenocytes express primary cilia, which elongate when tendon is maintained in the absence of biomechanical load. Previous work indicates differences in the morphology and metabolism of the tenocytes in the tendon fascicular matrix (FM) and the inter‐fascicular matrix (IFM). This study tests the hypothesis that primary cilia in these two regions respond differently to stress deprivation and that this is associated with differences in the biomechanical degradation of the extracellular matrix. Rat tail tendon fascicles were examined over a 7‐day period of either stress deprivation or static load. Seven days of stress deprivation induced cilia elongation in both regions. However, elongation was greater in the IFM compared to the FM. Stress deprivation also induced a loss of biomechanical integrity, primarily in the IFM. Static loading reduced both the biomechanical degradation and cilia elongation. The different responses to stress deprivation in the two tendon regions are likely to be important for the aetiology of tendinopathy. Furthermore, these data suggest that primary cilia elongate in response to biomechanical degradation rather than simply the removal of load. This response to degradation is likely to have important consequences for cilia signalling in tendon and as well as in other connective tissues. © 2016 The Authors. Journal of Orthopaedic Research Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 34:2146–2153, 2016.